Defect-induced transformation between hardening and softening behaviors in CuF2-doped K0.5Na0.5NbO3 piezoceramics. Issue 2 (1st February 2019) - Liao, You; Wang, Dongmei; Wang, Hua; Wang, Tao; Wei, Xianhua; Zheng, Qiaoji; Jie, Wenjing; Lin, Dunmin
Abstract: The hybrid-doped (Cu and F ions) piezoceramics of K0.5 Na0.5 NbO3 +  x % mol CuF2 (KNNCF- x ) were synthesized via an ordinary sintering technique, and the defect-driven transformation between hardening and softening behaviors and the corresponding mechanism were studied. The introduction of a small amount of CuF2 ( x  ≤ 1.5) generates two kinds of defect complexes (i.e., ( Cu Nb ′ ′ ′ − V O ∙ ∙ ) ′ (DC1) and ( V O ∙ ∙ − Cu Nb ′ ′ ′ − V O ∙ ∙ ) ∙ (DC2)). However, with x further increasing to 3.0, both DC1 and DC2 defect complexes gradually disappear. This variation of defect complexes with the doping level of CuF2 is resulted from the competition effect of the dopings of Cu and F ions. As a result of the evolution of DC1 and DC2 induced by the co-doping of Cu and F ions, the ferroelectric and piezoelectric behaviors of the ceramics exhibit interesting V-shape evolutions: as x increases, the P-E loop becomes more pinched until it forms a double hysteresis loop at x  = 1.5, while the double hysteresis loop gradually "opens" and becomes a normal slanted single one with x further increasing to 3.0; accordingly, the ceramics are gradually hardened with x increasing, showing an ultrahigh Q m (2708) and a low d 33 (91 pC/N) at x  = 1.50, but softened with x further increasing, providing a relatively low Q m (349) and a high d 33 (140 pC/N) at x  = 3.0.